Problems of Depicting Spatial Figures on a Plane - Iqboljon, Abdullayev (European Journal of Life Safety and Stability (2660-9630), 2021)
The interrelated study of the properties of plane and spatial figures is a means of solving the problem associated with the artificial division of school geometry into planimetry and stereometry. The psychological characteristics of middle school students indicate that the generally accepted practice of forming two-dimensional planar images of earlier three-dimensional spatial images disrupts the natural course of development of students' ideas about space. It turns out to be quite difficult to correct the firmly fixed methods of operating mainly with planar two-dimensional images in the process of studying stereometry